Correlation of Hypoxia and Pro-senescence Protein Expression in Green Sea Turtle (Chelonia mydas) Lung Epithelial and Dermal Fibroblast Cell Culture - Anggraini Barlian; Yemima Dani Riani (Institute for Research and Community Services (LPPM) ITB, 2018)
Recent studies have shown hypoxia-induced gene expression correlated with cellular senescence. HIF-1Î± (hypoxia-inducible factor 1-alpha), p53, and pRB were induced under hypoxia and correlated with cellular senescence. The localization and expression of HIF-1Î±, p53, and pRB in Chelonia mydas lung epithelial and dermal fibroblast cell cultures were analyzed under normoxic and hypoxic conditions (at 4 and 24 hours). Human dermal fibroblast was used for comparison purposes. Protein localization was analyzed with immunocytochemistry, while protein expression was analyzed with the Western blot and enhanced chemiluminescence (ECL) method. HIF-1Î±, p53, and pRB were localized in the nuclei of the C. mydas cell cultures treated with hypoxia. The C. mydas lung epithelial cell cultures had a higher increase of HIF-1Î± expression than the human dermal fibroblast cell culture. The hypoxic conditions did not affect p53 expression significantly in C. mydas lung epithelial and dermal fibroblast cell cultures. Meanwhile, pRB expression changed significantly under hypoxia in the C. mydas dermal fibroblast cells. Expression of p53 and pRB in the human cell cultures was higher than in the C. mydas cell cultures. This research suggests that C. mydas and human cell cultures have different pro-senescence protein expression responses under hypoxic conditions.